Digital Governance Model for Zakat Based on MUI Fatwas in Indonesia - Erni Juliana Al Hasanah Nasution (International Journal of Cyber ​​and IT Service Management (IJCITSM), 2025)
The rapid advancement of zakat digitalization in Indonesia has not received adequate support from comprehensive normative guidance. Against this backdrop, this research maps the disparities between the Council of Indonesia Ulama (MUI) fatwas and digitalization of zakat administration, while designing a governance model to bridge existing gaps. The study positions MUI as the central focus due to its status as the apex fatwa authority that confers Sharia legitimacy upon Islamic financial practices, including zakat operations. Methodologically, this research employs a qualitative multi-method design comprising systematic content analysis of 30 MUI zakat fatwas issued between 1982-2024, cross-jurisdictional comparative review of digital zakat governance frameworks, and thematic synthesis of primary materials (fatwas) and secondary sources (peer-reviewed articles and relevant regulations). The core findings demonstrate that only 6.7 percent of these fatwas directly and substantively address digitalization, indicating a material regulatory lacuna. The consequences encompass ambiguity regarding Sharia compliance, disincentives toward innovation, and fragmented standards in digital technology deployment and data governance within zakat institutions. In response, this paper proposes a Fatwa-Based Digital Zakat Governance Framework organized around three fundamental pillars: (1) Sharia-aligned digital innovation, (2) technology-enabled operational efficiency, and (3) digital accountability mechanisms. The framework incorporates a phased implementation roadmap and provides actionable guidance for practitioners and regulators. Overall, this model supports the sustainable digital transformation of Indonesia's zakat institutions while preserving Sharia compliance requirements.